1998
DOI: 10.1590/s0100-879x1998001000007
|View full text |Cite
|
Sign up to set email alerts
|

Short duration of neutralizing antibody titers after pre-exposure rabies vaccination with suckling mouse brain vaccine

Abstract: The human anti-rabies pre-exposure treatment currently used in Brazil, employing a 1-ml dose of suckling mouse brain vaccine (SMBV) administered on days 0, 2, 4 and 28, was compared to an alternative treatment with two 1 ml-doses on day 0, and one 1 ml-dose injected on days 7 and 21. The latter induced higher virus-neutralizing antibody (VNA) titers on day 21. Both Brazilian rabies vaccines produced with PV or CVS rabies virus strains were tested. Two additional volunteer vaccinee groups, receiving the pre-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Consequently, homology only existed between the vaccinal virus strain and the target strain for those serum samples from bovines immunized with IPVvac when neutralization assay was used for testing. We have recently reported that people receiving PM-cellculture had significantly higher VNA titers when their serum samples were tested against CVS strain than they did when they were tested against PV strain 21 , corroborating this supposition.…”
Section: Discussionsupporting
confidence: 58%
“…Consequently, homology only existed between the vaccinal virus strain and the target strain for those serum samples from bovines immunized with IPVvac when neutralization assay was used for testing. We have recently reported that people receiving PM-cellculture had significantly higher VNA titers when their serum samples were tested against CVS strain than they did when they were tested against PV strain 21 , corroborating this supposition.…”
Section: Discussionsupporting
confidence: 58%
“…This may be the result of inadequate courses of vaccine or a reduction of NAb levels after vaccination. The reduction of NAb levels was also reported by Zanetti and colleagues, who showed that after 180 days post vaccination, seroconversion could not be found in 60% of people who were vaccinated with four doses of suckling mouse-derived vaccine on day 0-0-7-21 [ 12 ]. Recently, atypical rabies transmission from animals to humans associated with the butchering and processing of dog meat has been reported in several parts of the world [ 4 , 13 – 15 ].…”
Section: Discussionsupporting
confidence: 61%
“…The inactivated suckling mouse brain rabies vaccine (SMBV) presents an adequate antigenic mass, producing immunity with few adverse side effects in the majority of the animal population 4 . Since a low immunogenic response had been observed in studies undertaken with individuals and animals immunized with the inactivated suckling mouse brain rabies vaccine, a booster dose was found necessary 5,6,7,8,9 . The SMBV is used in Brazilian national vaccination campaigns against rabies, in dogs and cats, carried out, annually, in September.…”
Section: Introductionmentioning
confidence: 99%